Kepemimpinan Kepala Sekolah dalam Upaya Meningkatkan Kompetensi Kewirausahaan Siswa - Hartawan, Rolifola Cahya (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2022)
This research is motivated by the low entrepreneurial competence of vocational students, so that it has an impact on the lack of vocational graduates who open new jobs. The approach in this study is descriptive qualitative, so the purpose of this study is to describe and analyze 1) the leadership characteristics of the principal of SMKN 1 and SMKN 4 Metro Lampung, 2) the principal's leadership strategy which includes the implementation of environmental analysis, strategy formulation, strategy implementation and strategy evaluation, 3) Superior entrepreneurship programs. SMKN, 4) the constraints faced, and 5) solutions to overcome these problems. The results of the study: 1) Principals of SMKN carry out transformational leadership 2) Principals have implemented a strategy to improve the quality of graduates but have not yet been formulated in the school RKS/RKAS. 3) The implementation of entrepreneurship programs in SMKN has been integrated with education and very high entrepreneurial values ​​and entrenched in schools. 4) There are several obstacles for school principals in an effort to improve students' entrepreneurial competencies. 5) There is a solution to overcome the obstacles for the Principal in an effort to improve the entrepreneurial competence of students. Keywords: Leadership, Transformational, leadership strategy